Manajemen Kualitas Islami Menjaga Konsistensi Produk Kopi Robusta - Purnomo, Hari; Alkhumaisi, Abduh (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyze the quality control (QC) management in maintaining the flavor consistency of Robusta Coffee products and examine its implementation according to the perspective of Sharia Economics at the X-Barue Kalibaru Home Industry. This descriptive qualitative research with a case study approach utilizes the Plan-Do-Check-Action (PDCA) cycle and flowchart analysis tools within the Total Quality Management (TQM) framework. Primary data sources were obtained through interviews and direct observation. Findings indicate that the X-Barue Home Industry successfully maintains flavor consistency through natural method-based control, supported by the disciplined application of the PDCA cycle at every processing stage. Essentially, the business practices observed, such as honesty, willingness to provide compensation (responsibility/guarantee), and high meticulousness, inherently reflect core Sharia values such as amanah (trustworthiness) and the maslahah (public interest) principle. The novelty of this study lies in modeling a holistic QC that integrates the technical discipline of quality management with Islamic business ethics. The implication is the strengthening of the Sharia Economics framework, demonstrating that sustainable product quality is an inseparable part of Islamic business practices.